Labour market dynamics in Australia: What drives unemployment - Marika Karanassou; Hector Sala (Queen Mary University of London, Department of Economics, 2009)
The debate in Australia on the (constant-output) elasticity of labour demand with respect to wages has wrongly sidelined the role of capital stock as a determinant of employment (Webster, 2003). As far back as 1991, Pissarides had argued that the influence of capital stock on the performance of the labour market is crucial but not well understood, a research area which is particularly relevant for Australia. This paper attempts to fill this void by estimating a multi-equation labour market model comprising labour demand, wage setting and labour supply equations. The model is used to examine the causes of the unemployment upturn in 1973-1983 and the subsequent decline in 1993-2006. Our results show that (i) the main determinants of the unemployment rise in the 1970s and early 1980s were wage-push factors, the two oil price shocks and the increase in interest rates, and (ii) the acceleration in capital accumulation was the crucial driving force of unemployment in the 1990s and 2000s. Furthermore, although the recent boom in the terms of trade is equally important, its downward effect on unemployment was partially reversed by the resulting decrease in net foreign demand.
Keywords: E22; E24; J21; 330; labour market dynamics; capital accumulation; chain reaction theory; Arbeitsmarkt; Arbeitslosigkeit; Arbeitsnachfrage; Lohnbildung; Investition; Wirtschaftliche Anpassung; Beschäftigungseffekt; Schätzung; Australien